Growth, Physiological, and Yield Responses of ‘Micro-Tom’ and Commercial Tomato Varieties Under High Temperature Conditions - Wahyu Muhammad Yuha Lubis; Dhika Prita Hapsari; Roedhy Poerwanto; Deden Derajat Matra (Department of Agronomy and Horticulture, IPB University, 2026)
Tomato, a nutrient-rich horticultural crop, is widely cultivated and consumed worldwide, with the ‘Micro-Tom’ cultivar commonly used as a model plant for its compact size and rapid life cycle. In tropical regions, rising temperatures caused by climate change intensify heat stress, which disrupts pollen viability and reduces fruit set, thereby limiting tomato productivity. This study aimed to evaluate the growth, physiology, and production responses of 'Micro-Tom' and three commercial tomato varieties 'Bareto' F1, 'Gustavi' F1, 'Tymoti' F1 under high temperature (HT) conditions. The experiment was conducted from March to November 2023 at the Leuwikopo Experimental Field, IPB Bogor, using a randomized complete block design with two factors (temperature and variety) and three replicates. For the HT treatment, plants were placed in a UV-protected plastic house, resulting in a minimum temperature of 18.7 °C and a maximum temperature of 46.2 °C. In contrast, the standard temperature (ST) treatment had a minimum temperature of 17 °C and a maximum temperature of 40.2 °C. The treatments lasted approximately three months, from transplanting to harvest. The standard temperature (ST) treatment outperformed the high-temperature (HT) treatment across all measured parameters, including plant height, leaf number, flower number, chlorophyll content, glucose and fructose levels, and fruit production. Among the varieties, ‘Bareto’ F1 exhibited superior performance across most parameters. Limitations of this study include its implementation in a controlled field setting over a single season. These findings highlight the need for further investigation into heat-tolerant genotypes and the physiological mechanisms that enhance tomato resilience under climate induced stress.